1999
DOI: 10.1007/bf02253525
|View full text |Cite
|
Sign up to set email alerts
|

A nontoxicPseudomonas exotoxin a induces active immunity and passive protective antibody againstPseudomonas exotoxin a intoxication

Abstract: Pseudomonas exotoxin A (PE) is one of the most potent cytotoxic agents produced by Pseudomonas aeruginosa. In this study, we examined the possibility of using PE with a deletion of 38 carboxyl-terminal amino acid residues, designated PE(Delta576-613), for active immunization against PE-mediated disease. We first examined the toxic effects of PE and PE(Delta576-613) on 5- and 9-week-old ICR mice. The results show that the subcutaneous administration of PE(Delta576-613) at a dose of 250 microg was still nontoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…It’s revealed that P. aeruginosa possesses various protein secretion systems to invade and damage host cells, of which the type II secretion system (T2SS) and type III secretion system (T3SS) secrete the majority of known toxins [23], [56], [57]. As an important cytotoxic extracellular protein, Exotoxin A also acquires effective immunogenicity, making it potential candidate for Pseudomonas vaccine [58]–[60]. PcrV is a key component of T3SS, regulating the assembly of virulence effector-delivery structure in eukaryotic cell membrane, besides, efficacy of anti-PcrV immunotherapy in animal of P. aeruginosa infection suggested the immune-protective feasibility of PcrV [36], [61].…”
Section: Discussionmentioning
confidence: 99%
“…It’s revealed that P. aeruginosa possesses various protein secretion systems to invade and damage host cells, of which the type II secretion system (T2SS) and type III secretion system (T3SS) secrete the majority of known toxins [23], [56], [57]. As an important cytotoxic extracellular protein, Exotoxin A also acquires effective immunogenicity, making it potential candidate for Pseudomonas vaccine [58]–[60]. PcrV is a key component of T3SS, regulating the assembly of virulence effector-delivery structure in eukaryotic cell membrane, besides, efficacy of anti-PcrV immunotherapy in animal of P. aeruginosa infection suggested the immune-protective feasibility of PcrV [36], [61].…”
Section: Discussionmentioning
confidence: 99%